Some recent finds of Bronze-Age metalwork from Perthshire (Proceedings of the Society of Antiquaries of Scotland, 1987)
Several bronze axes; a flanged chisel or hammer; a leaf-shaped sword; an important BA hoard from Clockmaden Farm, Collace (early Ewart Park phase, 9th-8th century BC); all in Perth Museum. F B